Country differences in the cross-sectional associations between smoking and depressive symptoms in adolescence. (4th November 2022) - Raffetti, Elena; Donato, Francesco; Triolo, Federico; Andersson, Filip; Forsell, Yvonne; Galanti, Maria Rosaria
Abstract: Background: The aim of the present study was to compare the cross-sectional association between smoking and depressive symptoms among adolescents between Sweden and Italy, two countries historically characterized by different norms about tobacco use and different tobacco control efforts. Methods: A cross-sectional study including 3283 adolescents 15–16 years of age participating in the Swedish KUPOL study and 1947 same-age adolescents from the Italian BE-TEEN study. Current smoking was defined as any smoking in the past 30 days. Depressive symptoms were assessed using the Centre for Epidemiological Studies Depression Scale for Children (CES-DC) and the internalizing score of the Strengths and Difficulties Questionnaire (SDQ). Country differences were explored in stratified and interaction analyses. Results: Current smoking was associated with a 2- to 3-fold increased odds of depressive symptoms among Swedish adolescents using both CES-DC and SDQ internalizing scale. Among Italian adolescents, slightly lower increased odds of 1.5–2.5 for depressive symptoms with smoking were found using the CES-DC but not the SDQ scale. Both multiplicative and additive interactions for country were significant. The association between smoking and depressive symptoms was weaker among Italian compared with Swedish adolescents for both scores. Conclusions: Countries with different tobacco norms and control show different associations between smoking and depressive symptoms in adolescence, probably due to different psychosocial profiles of smokers. These findings need to be considered when planning tobacco prevention programmes, e.g. by focusing on early detection of mental health distress among adolescents in settings with declining smoking prevalence and restrictive tobacco control environments.